SUPERVISIÓN BANCARIA EN LOS ESTADOS UNIDOS: VALORACIÓN DE LOS EFECTOS ECONÓMICOS DE MEDIDAS CORRECTIVAS EN EL DESEMPEÑO BANCARIO - Hall, Luis J. (2013)
This paper studies the effects of the 1991 Prompt Corrective Action in the banking system of the United States.  This law focuses on regulating those banks that have low capital ratios.  Two strategies are combined to properly identify these effects on the banking sector.  First, the design of the policy permits the appropriate evaluation of the impact of the law, since it creates the environment for using differences in differences.  Second, the technique of Propensity Score Matching is used to adequately select in a multidimensional scale the control group of the experiment.  The combination of these elements allows to identify and to evaluate the magnitude of the impact of this regulation.